Kepemimpinan Kepala Sekolah dalam Upaya Meningkatkan Kinerja dan Kompetensi Guru Pai di SMPN 1 Tembelang - Amirulloh, Moch. Ilmi; Chotimah, Chusnul; Lilawati, Emi (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The ability as a leader has the authority to move all components in the educational institution, especially in maximizing the performance of teachers and the competencies they hold. Therefore, the aim of this research is to look at, observe and examine the leadership of school principals in an effort to increase the effectiveness and proficiency of Islamic religious education teachers. The elements studied were the competency of Islamic Religious Education teachers, teacher performance, and school principal leadership. The researchers used curriculum heads, school principals, and Islamic Religious Education teacher subjects in a descriptive qualitative research methodology. Researchers collect data through interviews, documentation and observation. The data analysis method for this research's conclusions was drawn through data reduction, data presentation, and drawing conclusions. Research findings show that the leadership of the school principal as a mover, director, motivator, mentor is able to maximize his role and function in order to improve the quality and performance of Islamic religious education teachers. The performance and competence of Islamic religious education teachers at SMPN 1 Tembelang Jombang meets the criteria as a competent teacher in their field through the leadership of a competent principal in carrying out his duties. The principal at SMPN 1 Tembelang Jombang improved the performance and competence of PAI teachers through affirmation of attending MGMP, seminars, workshops and workshops. He encourages academic supervision, providing feedback, and holding one-on-one conversations.